A rare association of uterine leiomyoma with mesenteric vein thrombosis and bowel gangrene: case report - Rawat, Rajneesh; Gedam, Manik; Baghel, Jyoti; Baghel, Shalini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Uterine fibroids are the most common benign pelvic tumors in women. There are many complications reported with fibroids. However, mesenteric vein thrombosis and small bowel gangrene caused by a uterine fibroid are rare. This manuscript reports a rare case of 40 year female with a large uterine fibroid associated with mesenteric vein thrombosis and bowel ischemia. She underwent exploratory laparotomy in which resection of gangrenous bowel including jejunum and ileum was done along with left sided jejunostomy and right sided ileostomy. Total abdominal hysterectomy with bilateral salpingooophorectomy was done followed by jejunoileal anastomosis 6 weeks later. Hence, in patients presenting with acute abdomen and uterine fibroids, bowel gangrene must be included in the differential diagnosis.